Von Hippel–Lindau Disease - Findeis-Hosey, Jennifer J.; McMahon, Kelly Q.; Findeis, Sarah K. (Journal of Pediatric Genetics, 2016)
Von Hippel–Lindau disease is an autosomal dominant syndrome which occurs secondary to germline mutations in the VHL tumor suppressor gene, located on chromosome 3. Clinically von Hippel–Lindau disease is characterized by an increased risk of developing simple visceral cysts, most commonly in the pancreas and kidneys, in addition to an increased risk of developing neoplasms, often with clear cell features, in a multitude of organ systems. The most common neoplasms are cerebellar and retinal hemangioblastomas, adrenal pheochromocytomas, clear cell renal cell carcinomas, pancreatic neuroendocrine tumors, pancreatic serous cystadenomas, and endolymphatic sac tumors. These lesions most commonly present during adulthood; however, screening and surveillance for the development of these lesions should begin in the pediatric years for patients with von Hippel–Lindau disease. In this review article, the genetics and most common neoplasms of von Hippel–Lindau disease are reviewed, with an eye towards implications for the pediatric patient.
Keywords: von Hippel–Lindau; pathology; pediatric